2008
DOI: 10.1007/s11199-008-9507-2
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Empathic Bias, Empathic Inaccuracy, and Sexual Harassment

Abstract: This study investigated the relationship between men's sexual harassment of women and men accuracy and bias when inferring women's critical or rejecting thoughts and feelings. Eighty married men from the Arlington, Texas, USA community participated. Results indicated that men's sexual harassment behavior is negatively related to men's accuracy in determining when women have critical or rejecting thoughts or feelings. Further, men's sexual harassment behavior is positively related to men's bias to overattribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…3 Why more highly educated women here were more likely to be harassed is unclear; these women may more often be employed in male-dominated settings, be more knowledgeable about what constitutes sexual harassment, or be perceived as threatening, as sexual harassment is an assertion of hierarchical power relations. 3,26 …”
Section: Discussionmentioning
confidence: 99%
“…3 Why more highly educated women here were more likely to be harassed is unclear; these women may more often be employed in male-dominated settings, be more knowledgeable about what constitutes sexual harassment, or be perceived as threatening, as sexual harassment is an assertion of hierarchical power relations. 3,26 …”
Section: Discussionmentioning
confidence: 99%
“…1997; Pryor and Whalen 1997). Harassers are also thought to over‐infer women's criticism and rejection, supporting the view that SH is related to aggression rather than seduction (Schweinle et al . 2009).…”
Section: Characteristics Of Harassers and Complainants And Perceptionmentioning
confidence: 70%
“…However, some studies have suggested that harassers lack social conscience, are naïve about heterosexual relationships, and engage in immature, irresponsible, manipulative and exploitative behaviours (Begany and Milburn 2002;Kosson et al 1997;Pryor and Whalen 1997). Harassers are also thought to overinfer women's criticism and rejection, supporting the view that SH is related to aggression rather than seduction (Schweinle et al 2009). No parallel research has been conducted on women who harass men (Foote and Goodman-Delahunty 2005).…”
Section: Characteristics Of Complainants and Harassersmentioning
confidence: 97%
“…Many scholars argue that sexual harassment is a form of aggressive and violent behavior (e.g., Farley, 1978;Fitzgerald, 1993;Kelly, 1988;Krings & Facchin, 2009;OÕLeary-Kelly, Paetzold, & Griffin, 2000;Quina, 1990;Schweinle, Cofer, & Schatz, 2009). …”
Section: Sexual Harassment As Goal Motivated Behaviormentioning
confidence: 99%